A Case of Postoperative Endophthalmitis Caused by Streptococcus Bovis. (2nd January 2023) - Liu, Guangsen; Li, Yue; Gao, Lei; Li, Na; Su, Jing
ABSTRACT: Purpose: To report a case of postoperative endophthalmitis caused by Streptococcus bovis (S. bovis). Methods: Retrospective case report. Results: A 50-year-old healthy man presented with endophthalmitis 16 hours after silicone oil removal. Vitreous cultures remained positive for S. bovis. In addition to vitreous and anterior chamber lavage, the patient received five intravitreal injections in total. All the above aggressive measures did not effectively prevent the deterioration of the disease and the patient was discharged with a final outcome of retinal detachment and atrophia bulbi with no light perception. Conclusions: To the best of our knowledge, this is the first report of postoperative endophthalmitis caused by S. bovis.